Pakistan’s Role in United Nations Peacekeeping Missions: An Appraisal - Bekele Jemallu Jenber; Hashmat Ullah Khan (ASIAN Journal of International Peace & Security (AJIPS), 2021)
In the post, Second World War era peacekeeping missions are playing crucial role in preserving peace in the world and in the solution of conflicts in conflicted regions and states. Different United Nations member countries, including Pakistan, are contributing to these missions. The main aim of this study is to explore the contributions and role of Pakistan in the UN peacekeeping missions. This study tries to answer why Pakistan is participating in UNPKOs and the contributions of Pakistan in these operations. One of the main aims of the foreign policy of Pakistan is to maintain global security and peace. Therefore, it is actively participating in United Nations peacekeeping missions since its inception. Pakistan has contributed to a total of 46 missions in 28 different countries and regions which played a very important role in preserving global peace and security. By their patient manners and high level of professionalism,Pakistani peacekeepers have conducted many successful missions and won the minds and hearts of the local population and got huge appreciation internationally. To date 157 Pakistanis also lost their lives in this noble cause.